Qualitative observations of the cirrus clouds effect on the thermal structure of the tropical tropopause. (December 2020) - Ali, Saleem; Mehta, Sanjay Kumar; Annamalai, Vanmathi; Ananthavel, Aravindhavel; Reddy, Ramesh
Abstract: An attempt has been made to understand the effect of the cirrus clouds on the tropical tropopause thermal structure over a tropical station Gadanki (13.45 o N, 79.2 o E) using regular radiosonde observation at 12:00Z and CALIPSO measurements at the closest proximity to Gadanki during 2006–2013. As the CALIPSO and radiosonde observation timings are not simultaneous, we considered only those cases when cirrus clouds are appeared both during daytime and nighttime over Gadanki. In total 45 simultaneous cirrus clouds and temperature observations are found. Out of which 24 cases are found with cirrus clouds top within 1.0 km of cold point tropopause (CPT; called tropopause cirrus) and 16 cases are below 2.0 km of CPT. The tropopause cirrus is further classified into geometrically thin (thick) cirrus clouds based on its thickness less (greater) than 2.0 km. Out of them 9 and 15 cases are found as geometrically thin and thick cirrus, respectively. The temperature profiles for geometrically thin, thick and the cases with cirrus below the tropopause show different structure from the clear-sky temperature profile. The mean difference between temperature gradients of geometrically thin and thick cases with clear-sky shows a distinct peak near the tropopause which coincides with the peak of mean volume depolarization ratio indicating that tropopause cirrus modifies the tropopause structure. Finally, the relationship between various tropopause parameters with cirrus cloud top height is obtained. For the tropopause cirrus cases, CPT becomes warmer by ~1.2 K, COT rises by 0.8 km, TTL thickness (temperature) decreases (increases) by ~0.9 km (2.2 K) with increase in the cloud optical thickness and cloud radiative forcing. However, TTL becomes relatively colder and thicker for the cirrus clouds occurring below the tropopause. Highlights: Using radiosonde and CALIPSO observations, we report the qualitative estimates of cirrus clouds effect on the tropical tropopause. Presence of tropopause cirrus clouds observed to be altering the temperature gradient in the tropopause region. For the tropopause cirrus cases, CPT becomes warmer by ~1.2 K, COT rises by 0.8 km, TTL thickness (temperature) decreases (increases) by ~0.9 km (2.2 K) with increase in the cloud optical thickness and cloud radiative forcing. However, TTL becomes relatively colder and thicker for the cirrus clouds occurring below the tropopause.